Vasculitic Neuropathies - Beachy, Nathaniel; Satkowiak, Kelsey; Gwathmey, Kelly Graham (Seminars in Neurology, 2019)
Vasculitic neuropathies are disorders that result from inflammation in the peripheral nerves' vascular supply, resulting in ischemic injury. These disorders may be a result of systemic inflammation or may be confined to the peripheral nervous system. Causative etiologies include primary systemic vasculitis, vasculitis secondary to other conditions such as primary connective tissue disorders, infectious, paraneoplastic, and drug-induced conditions, and nonsystemic vasculitic neuropathy. Early recognition and treatment of these conditions is imperative to prevent substantial morbidity and mortality. The goal of this review is to provide an organization of the vasculitic neuropathies and an overview of principles of diagnosis and treatment for the clinical neurologist.
Keywords: vasculitic neuropathy; vasculitis; nonsystemic vasculitic neuropathy; microvasculitis; nerve large arteriole